German Validation of the Conners Adult ADHD Rating Scale–Self-Report: Confirmation of Factor Structure in a Large Sample of Participants With ADHD. (November 2013) - Christiansen, Hanna; Hirsch, Oliver; Philipsen, Alexandra; Oades, Robert D.; Matthies, Swantje; Hebebrand, Johannes; Ueckermann, Jennifer; Abdel-Hamid, Mona; Kraemer, Markus; Wiltfang, Jens; Graf, Erika; Colla, Michael; et al.
Objective: The Conners Adult ADHD Rating Scales (CAARS) assess symptoms specific to adults that are frequently used and have been translated into German. The current study tests the factor structure of the CAARS in a large sample of German adults with ADHD and compares the means of the CAARS subscales with those of healthy German controls.Method: CAARS were completed by 466 participants with ADHD and 851 healthy control participants. Confirmatory factor analysis was used to establish model fit with the American original. Comparisons between participants with ADHD and healthy controls and influences of gender, age, and degree of education were analyzed.Results: Confirmatory factor analysis showed a very good fit with the model for the American original. Differences between ADHD participants and healthy controls on all Conners Adult ADHD Rating Scales–Self-Report (CAARS-S) subscales were substantial and significant.Conclusion: The factor structure of the original American model was successfully replicated in this sample of adult German ADHD participants.